Development and performance of perovskite cathode with application towards gas purification: article - Shamsuri, Nurul Nazaha; Mohd Akhir, Ammar (2019)
Solid Oxide Fuel Cell is one of the most advantages fuel cell as it is low pollutant emission, low noise, easy to produce and high energy performance. The research developed based on SOFC is to reduce its operating temperature as high temperature will reduce the performance of the cell. One of the most used material to make SOFC is Lanthanum Strontium Cobalt Ferrite (LSCF). LSCF is mixed with starch and Polyvinyl Alcohol as binder to be made into pellet which then will be sintered at temperature range of 600˚C to 750˚C which are the right temperature range for this study as temperature over 800˚C is said to be damaging the materials and therefore reducing the performance of the cathode. The samples will be tested using the X-ray Diffraction (XRD). The electrical conductivity was measured using the Electrochemical Impedance Spectrometer (EIS). For the XRD data, it can be concluded that the size of the particle increases as the temperature increases from 31.18 nm to 38.64 nm. The size starts to decrease to 36.33 nm at 750˚C. Based on the XRD profile, it can see that the highest peak for all different sintering temperature are around 2θ= 32˚ suggesting that they are of the same purity of metal and perovskite structure. For the EIS data profile, the electrical conductivity increase at 600˚C to 700˚ from 4.4987x10-5 Ω/cm to 7.7916x10-5 Ω/cm and then decreases at 750˚C to 6.8640x10-5 Ω/cm. It is evident that the increase in electrical conductivity of the fabricated LSCF is parallel with the literature report. The findings are indicating that the pellet is starting to degrade at temperature 750˚C.